2011
DOI: 10.1007/s11661-011-0663-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Particle-Reinforced Transient Liquid Phase Diffusion Bonding: a Comparative Study

Abstract: Particle-reinforced aluminum-metal matrix composites (Al-MMCs) are used in many engineering applications, because they provide significant advantages when compared to monolithic aluminum alloys. However, there still exists the need to identify a suitable joining process for these materials, which minimizes particulate disruption and retains the strength of the MMC within the joint region. This study presents a comparison between joint qualities achieved when a monolithic interlayer is used vs when a nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This increase in joint shear strength was attributed to better distribution of nano-sized particles within the interlayer when smaller particle sizes are used. In both cases higher shear strengths were obtained than when pure Ni coating is used (117 MPa) [23]. The results indicate that joint strength of up to 90% that of the base metal (BM) is achievable when using a 50 nm diameter nano-sized particle-reinforced interlayer.…”
Section: Effect Of Coating Thickness On Shear Strength Measurementsmentioning
confidence: 84%
See 3 more Smart Citations
“…This increase in joint shear strength was attributed to better distribution of nano-sized particles within the interlayer when smaller particle sizes are used. In both cases higher shear strengths were obtained than when pure Ni coating is used (117 MPa) [23]. The results indicate that joint strength of up to 90% that of the base metal (BM) is achievable when using a 50 nm diameter nano-sized particle-reinforced interlayer.…”
Section: Effect Of Coating Thickness On Shear Strength Measurementsmentioning
confidence: 84%
“…A high resolution SEM micrograph shown in Figure 5 revealed the presence of a nano-sized alumina particle at the center of a grain. EDX spectra of the particle showed Al and O in high concentrations with traces of Mg [23,24,33]. Comparing Gibbs free energy of formation at the bonding temperature for MgO (-1195 kJ/mol) and Al2O3 (-985 kJ/mol) it is found that Al2O3 is unstable in the presence of Mg hence it is like that some of the nano-size Al2O3 will decomposed to form MgAl2O4 compound.…”
Section: Advanced Aspects Of Spectroscopy 318mentioning
confidence: 96%
See 2 more Smart Citations
“…In recent years, some researchers succeeded in reinforcing bond seam by externally adding ceramic particle into monolithic interlayer [24][25][26][27][28][29][30][31]. In contrast, in-situ reinforcing phase formed within the bond seam has clean interface and resultant excellent wettability with bond seam matrix [32].…”
Section: Introductionmentioning
confidence: 99%